EFEKTIFITAS PEMBERIAN KOLOSTRUM DENGAN ANGKA KEJADIAN DIARE PADA BAYI 0-6 BULAN DI DUSUN V DESA BANGUN REJO KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG TAHUN 2018 - Siska Suci Triana Ginting (LP2MTBM MAKARIOZ, 2019)
The Indonesian National Children's Program makes the issue of infant and toddler deaths one of the most important parts. In Indonesia diarrheal disease is one of the main causes after respiratory tract infections which is around 45%. Though this disease can be prevented by giving ASI. Research shows early breastfeeding / colostrum reduces diarrhea. This study aims to determine the extent of the relationship between giving colostrum to the incidence of diarrhea in infants 0-6 months in Hamlet V, Bangun Rejo Village, Tanjung Morawa District, Deli Serdang Regency in 2012. This research is descriptive correlation with 32 respondents. In this study the analysis used is the correlation statistical test used is the Pearson test. From the results of this study it was found that the majority of respondents gave as many as 29 people (90.62%), and the minority did not give as many as 3 people (9.37%). Respondents in the light category were 32 people (100%). The results of this study state that the strength of the relationship is very strong and has a negative relationship direction (r-0.545) so that the higher the rate of colostrum the lower the incidence of diarrhea. There is a significant relationship between giving colostrum with the incidence of diarrhea in infants 0- 6 months (p <0.005).